THE MODEL OF FAITHFULNESS FOR BUDDHIST IN SCANDINAVIA COUNTRIES - Nyanaviro (Tanodkaew), PhrapaladKlanarong; Dhanapañño, PhramahaSombat; Srivichai, Suddhipong; Chirakulo (Jongsakulsiri), PhramahaPadet (Journal of Educational Review Faculty of Education in MCU, 2021)
The purpose of this research was to propose a model of faithfulness for Buddhist in Scandinavian countries. Mixed methods research with 3 steps was designed which were Step 1: Study the current situation and the problem of Buddhists' faith in Scandinavia using interview 6 key informants who were selected by purposive sampling. Step 2 Developed model by focus group discussion with 17 experts with purposive sampling. Step 3 examining and presenting the Buddhist faith-building model in the Scandinavian countries. The model evaluation was assessed from a sample of 300 Buddhists in Scandinavia. Data were analyzed by using frequency, percentage, mean and standard deviation. Research results showed that a model of faithfulness for Buddhist in Scandinavian countries consisted of Part 1 introduction included 1) the environment, 2) the principles, 3) the objectives. Part 2 the model included 1) the operating system, 2) the process of building faith in 4 areas: practice routines, regular activities, practice five universal basic goodness as a habit, Knowledgeable in the dharma, self-practice and friendly. Part 3 application process included 1) structure, 2) decision, and 3) evaluation guidelines.